Prevalence of hepatitis C among pregnant females attending antenatal clinic at a tertiary care hospital in Lucknow, Uttar Pradesh, India - Jahan, Noor; Chaudhary, Nitin; Nigar, Asma; Ahmad, Siraj; Khatoon, Razia; Kumar, Anil (International Journal of Advances in Medicine, 2020)
Background: Hepatitis C virus (HCV) is a major causative agent of parenterally acquired hepatitis. Vertical transmission of HCV occurs from mother to infant during pregnancy, delivery, or neonatal period. Hepatitis C infection among pregnant females can adversely affect both mother and fetus, leading to chronic infection in infants who later develop liver cirrhosis and hepatocellular carcinoma. Objective of the study was to evaluate the prevalence of hepatitis C among pregnant females attending antenatal clinic. Methods: A hospital based cross-sectional study was done over a period of six months from January to June 2019. A total of 550 pregnant females were included in the study who attended Antenatal Clinic for routine check-up and whose blood samples were sent to Microbiology Laboratory for screening of anti-HCV antibodies by Enzyme linked Immunosorbent Assay (ELISA) method. Results: Out of 550 pregnant females tested, 3 were found to be reactive to anti-HCV antibodies by ELISA; hence the prevalence was found to be 0.5%. All 3 seropositive females belonged to age group 26-35 years, were indoor patients (IPD) and belonged to lower socio-economic class. Majority of seropositive females belonged to urban areas (66.7%, 2/3) as compared to those from rural areas (33.3%, 1/3). Conclusions: Although, prevalence of hepatitis C was found to be less among pregnant females attending ANC of this institute, still routine screening of all pregnant females for anti-HCV antibodies is highly recommended, for timely detection of disease in mothers and prevention of its transmission to infants.